SEJARAH PERKOTAAN: SEBUAH TINJAUAN HISTORIOGRAFIS DAN TEMATIS - Ilham Daeng Makkelo (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
The growth of cities since the beginning of the 20th century has experienced rapid complexity of their elements and problems. Cities are not as simple as they used to be. Complexity in various fields requires methods and analytical knifes that can trace and expose parts and structures of urban areas to their smallest details and also to show their meanings to reveal structural relations which usually are complicated. One of my focus here is to pay attention to urban problems and theirinhabitants that increasingly becoming more complex, through the concept of modernity. Modern, modernization, modernism and modernity are historcal concepts that being used to read and to unravel the complexity in different periods. My using of the concept of modernity is an effort to explain in various ways the complex reality of urban history in Indonesia